Development, Evaluation and Characterization of Surface Solid Dispersion for Solubility and Dissolution Enhancement of Nifedipine - Dumbre, Ketaki A.; Gadhave, M. V; Gaikwad, D. D (Asian Journal of Pharmaceutical Research and Development, 2014)
The main objective of the study was to enhance the dissolution of nifedipine, a poorly water soluble drug by surface solid dispersion technique using different carriers and to study the effect of each carrier on the in vitro dissolution profile. The formulations were optimized in the preliminary trials by using various ratios of different carriers like cross carmellose sodium, crosspovidone, and sodium starch glycolate. Resultant formulations were evaluated using FTIR, X‐ray diffraction, DSC, SEM and in vitro dissolution. Solid dispersion with at 1:5 ratio gave good release when compared to pure drug and physical mixtures. The optimized dispersion was formulated in to sublingual tablets by using crosspovidone, crosscarmellose sodium and sodium starch glycolate as disintegrants and was evaluated for friability, hardness, weight variation, disintegration and in vitro dissolution